2021
DOI: 10.1039/d1ob01716k
|View full text |Cite
|
Sign up to set email alerts
|

A multifunctional divergent scaffold to access the formal syntheses of various sesquiterpenoids

Abstract: The development of a divergent scaffold able to access an array of diverse natural sesquiterpenoids is described. The route unifies the scope of previously reported plans of our group to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…16 The group highlighted the efficiency of the method in the synthesis of the common scaffold 36 that served as a multipurpose intermediate for total syntheses and for accessing sesquiterpenoid core structures (Scheme 3). 17 More specifically, acrylic acid 34 reacts with PIDA and iodine to form intermediate 35 , which can be photochemically cleaved to provide a long-lived carboxyl-radical able to initiate a 1,5-hydrogen atom transfer to the respective iodide (structure not shown). The latter is readily cyclized under the reaction conditions to allow the synthesis of 36 in 45% yield (78% brsm).…”
Section: Hofmann–loffler–freytag (Hlf) Reaction–suarez Modificationmentioning
confidence: 99%
See 2 more Smart Citations
“…16 The group highlighted the efficiency of the method in the synthesis of the common scaffold 36 that served as a multipurpose intermediate for total syntheses and for accessing sesquiterpenoid core structures (Scheme 3). 17 More specifically, acrylic acid 34 reacts with PIDA and iodine to form intermediate 35 , which can be photochemically cleaved to provide a long-lived carboxyl-radical able to initiate a 1,5-hydrogen atom transfer to the respective iodide (structure not shown). The latter is readily cyclized under the reaction conditions to allow the synthesis of 36 in 45% yield (78% brsm).…”
Section: Hofmann–loffler–freytag (Hlf) Reaction–suarez Modificationmentioning
confidence: 99%
“…Subsequent alkylation of both resulted in 41a and b and 43 that served as points of divergence to access germacranolides and guaianolides through oxy–Cope reactions 16 and furo sesquiterpenoids by cycloisomerizations. 17 Worth mentioning is the ability of sulfur-ylides to serve as convenient precursors for C-6 oxidation.…”
Section: Hofmann–loffler–freytag (Hlf) Reaction–suarez Modificationmentioning
confidence: 99%
See 1 more Smart Citation
“…With multigram quantities of ( R )-carvonic acid ( 4 ) in our hands, we next turned our attention to the key direct syn -8,12-lactonization step. To scale this reaction up, the NBS radical allylic bromination/cyclization sequence to afford 8 previously developed by our group resulted in inconsistent results and low yields (28%). Attempts to optimize the yield by direct allylic oxidation and carboxyl as a directing group to induce CH lactonization by known protocols failed to provide the desired 8,12-lactone.…”
mentioning
confidence: 99%
“…Earlier studies from our group revealed that the utilization of the oxy-Cope reaction and a subsequent ene-reaction in unnatural elemane 1 can provide a convenient route to the synthesis of furan germacrane and Asteraceae guaiane-type sesquiterpenoids (Scheme ). Analysis of the stereochemical outcome of the delivered Asteraceae guaianes in these processes led to knowledge that the tertiary carbon at 1-position was the crucial element for achieving high stereocontrol. Consequently, elemane 5 bearing an epimeric tertiary center at the 1-position was projected as an ideal candidate for accessing Apiaceae sesquiterpenoids (Scheme ).…”
mentioning
confidence: 99%